Analisis Pengungkapan Sustainable Development Goals dan Tata Kelola Perusahaan di Perusahaan Financial Technology - Suhardjo, Iwan; Meiliana, Meiliana; Meiviana, Meiviana; Derista, Fanny; Frederica, Vivian; Sulistiyowati, Riris (E-Jurnal Akuntansi, 2024)
The research aims to investigate the impact of Disclosure of Sustainable Development Goals (SDGs) and Corporate Governance on the performance of FinTech companies in Indonesia. This research took the population of FinTech companies on the Indonesia Stock Exchange (BEI) that published sustainability reports for 2020-2022, namely 7 companies. Tests using the multiple regression method as research results show that SDGs disclosure has a negative impact on company performance in the short term because switching to sustainable practices requires significant initial investment. In addition, corporate governance has a positive impact on company performance because good governance is believed to increase operational efficiency thereby increasing profits for the company. Keywords:Sustainable Development Goals; Corporate Governance; Company Performance